Association between dietary inflammation index and female infertility from National Health and Nutrition Examination Survey: 2013-2018 - Qi, Jie; Su, Yujie; Zhang, Huanhuan; Ren, Yanan (Frontiers in Endocrinology, 2024)
To investigate the relationship between dietary inflammatory index (DII) scores and infertility in US adults aged 18 to 45.Data were gathered from the 2013-2018 National Health and Nutrition Examination Survey (NHANES). In total, 3496 women were included in the study. To examine the relationship between DII, EDII and infertility, a weighted multivariable logistic regression analysis using continuous factors or categorical variables grouped by quartiles was conducted. Using subgroup analysis stratified based on DII and infertility features, the association between DII and infertility has been further studied. In order to determine whether there was a nonlinear relationship between DII and infertility, restricted cubic spline (RCS) analysis was carried out.For statistical analysis, a total of 3496 individuals -367 patients with infertility and 3129 persons without infertility -were included. A multivariable logistic regression study revealed a positive relationship between DII and infertility. A significant difference in subgroup analysis was shown in age group and race, although RCS analysis demonstrated nonlinear relationship between the DII and infertility.For participants aged 18-45 years, higher DII scores were positively correlated with infertility. In addition, antiinflammatory diets might improve infertility outcomes.